Pengaruh Kualitas Produk dan Ketersediaan Produk Terhadap Kinerja Operasional di Alfamart Area Pondok Kelapa - Alifatu Zandra Sapuwani; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study was conducted to determine the extent to which product quality and availability influence operational performance at Alfamart in the Pondok Kelapa area. Data were obtained through questionnaires distributed to respondents, employees of Alfamart outlets in the Pondok Kelapa area.The data analysis technique used were simple linear regression and multiple regression to measure the simultaneous and partial effects of each independent variable on the dependent variable. The results indicate that both product quality and availability have a positive and significant impact on operational performance